Potential tourism route planning based on Weka 3.8 application in Bangli Regency - Wibby Prasetya; I Wayan Eka Mahendra; Yohannes Kristanto; I Nengah Dasi Astawa (Institute of Computer Science (IOCS), 2023)
The aim of this research is to identify tourist travel routes in Bangli Regency, as well as planning potential tour packages for Bangli Regency. To collect data in this study, we used qualitative methods by distributing questionnaires offline, conducting direct interviews to 271 tourists visiting Bangli Regency. we used weka3.8 application-based market basket analysis and GIS mapping to visualize and analyze routes. We found that Bangli Regency has a variety of tourist attractions both natural attractions and cultural attractions. The attractions in this regency are no less interesting than other attractions in Bali. However, the description of this research shows that, only a few tourist objects are known and visited by tourists. the rest is almost not even heard at all in the ears of tourists. this is because most travel agents direct tourists to tourist objects that are just that - that's all. therefore, the results of this study create a potential tourist route plan which can later direct tourists to attractions that have potential but are not yet widely known by tourists. Similar studies that have been conducted by researchers out there the majority only examine the routes in Bangli Regency. there is no planning related to tourist routes there. so this research designs potential tourist routes in Bangli Regency.